2021
DOI: 10.1155/2021/7036059
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Cancer Stemness-Related Signature for Predicting Prognosis in Patients with Colon Adenocarcinoma

Abstract: Objective. To explore the cancer stemness features and develop a novel cancer stemness-related prognostic signature for colon adenocarcinoma (COAD). Methods. We downloaded the mRNA expression data and clinical data of COAD from TCGA database and GEO database. Stemness index, mRNAsi, was utilized to investigate cancer stemness features. Weighted gene coexpression network analysis (WGCNA) was used to identify cancer stemness-related genes. Univariate and multivariate Cox regression analyses were applied to const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…These results were then used to calculate the AUC values to assess whether the signature could successfully predict the overall survival of COAD patients in the training cohort. The AUCs of our laRlncRNA pairs-based signature for 1, 3, and 5 years were 0.749, 0.752and 0.772, respectively, whereas those obtained in three other lncRNA-based signature studies on COAD patients were much lower, which were ZhangLncSig ( 76 ), WangLncSig ( 77 ) and XingLncSig ( 78 ), respectively in Figure 4F ( Figure S3 showed the GEO cohort validation results) . In comparison to other traditional clinical pathological variables, the AUCs of our risk signature showed great accuracy in predicting prognosis of patients with COAD ( Figure 4G ) .…”
Section: Resultsmentioning
confidence: 80%
“…These results were then used to calculate the AUC values to assess whether the signature could successfully predict the overall survival of COAD patients in the training cohort. The AUCs of our laRlncRNA pairs-based signature for 1, 3, and 5 years were 0.749, 0.752and 0.772, respectively, whereas those obtained in three other lncRNA-based signature studies on COAD patients were much lower, which were ZhangLncSig ( 76 ), WangLncSig ( 77 ) and XingLncSig ( 78 ), respectively in Figure 4F ( Figure S3 showed the GEO cohort validation results) . In comparison to other traditional clinical pathological variables, the AUCs of our risk signature showed great accuracy in predicting prognosis of patients with COAD ( Figure 4G ) .…”
Section: Resultsmentioning
confidence: 80%
“…Meflin has been also reported to correlate with favorable prognosis and therapeutic response to immune checkpoint blockage treatment in patients with non-small cell lung cancer (NSCLC) ( Miyai et al, 2022 ). Alternatively, meflin is determined as an unfavorable gene with a predictive value in patients with colon adenocarcinoma ( Wang et al, 2021 ). Consistently, univariate Cox regression analysis revealed that meflin ( ISLR ) served as an unfavorable gene in LGGs in our research.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al verified that high levels of MFAP4 expression predict platinum-based chemotherapy resistance and imply a poor prognosis in patients with serous OC [ 45 ]. CCDC80 is a common tumor stemness marker used in a variety of solid tumor prognostic models [ 46 , 47 , 48 ]. Studies have shown that it helps tumor cells acquire drug resistance and immune infiltration [ 46 ].…”
Section: Discussionmentioning
confidence: 99%